Density, spin and isospin correlations in low-density two-component Fermi superfluid - Isayev, A.A.; Yang, J. (Физика низких температур, 2006)
Finding the distinct features of the crossover from the regime of large overlapping Cooper pairs
to the limit of non-overlapping pairs of fermions (Shafroth pairs) in multi-component Fermi systems
remains a topical problem in a quantum many-body theory. Here this transition is studied by
calculating the two-body density, spin and isospin correlation functions in dilute two-component
Fermi superfluid, taking as an example an infinite system of protons and neutrons (nuclear matter).
It is shown that criterion of the crossover (Phys. Rev. Lett. 95, 090402 (2005)), formulated
for ultracold fermionic atomic gases and consisting in the change of the sign of the density correlation
function at low momentum transfer, fails to describe correctly the density-driven BEC–BCS
transition at finite isospin asymmetry or finite temperature. As an unambiguous signature of the
BEC–BCS transition, one can use the presence (BCS regime) or absence (BEC regime) of the singularity
in the momentum distribution of the quasiparticle density of states.